2018
DOI: 10.1093/eurheartj/ehx762
|View full text |Cite|
|
Sign up to set email alerts
|

Telemonitoring-based feedback improves adherence to non-vitamin K antagonist oral anticoagulants intake in patients with atrial fibrillation

Abstract: Telemonitoring resulted in high NOAC adherence due to the notion of being watched, as evidenced by the rapid decline during the observation period. Feedback further optimized adherence. Telemonitoring with or without feedback may be a cost-effective approach in high-risk patients deemed poorly adherent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 29 publications
3
42
0
1
Order By: Relevance
“…Another study by Shore et al, although not prospective, showed that enhanced pharmacist involvement with a longer monitoring and follow-up of patients was associated with an improved adherence to dabigatran [ 24 ]. Third, a prior study by our group showed that daily telemonitoring of medication intake with direct personalized telephone feedback led to very high NOAC adherence values with a taking adherence and regimen adherence of 99.0% and 96.8%, respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Shore et al, although not prospective, showed that enhanced pharmacist involvement with a longer monitoring and follow-up of patients was associated with an improved adherence to dabigatran [ 24 ]. Third, a prior study by our group showed that daily telemonitoring of medication intake with direct personalized telephone feedback led to very high NOAC adherence values with a taking adherence and regimen adherence of 99.0% and 96.8%, respectively [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the AEGEAN study, the double-blind aspect of the study meant that adherence data feedback was not possible. However, a recently published telemonitoring study using daily patient feedback and employing an EMD showed very high adherence (89.6% over a 3-month observation period) to NOAC therapy despite the small sample size, probably largely attributable to being monitored [18]. Implementation adherence and persistence rates reported with VKAs are generally lower than those with NOACs, with historical cohort studies and clinical trials reporting rates of 42-78% (duration of follow-up of 3-84 months) [9].…”
Section: Discussionmentioning
confidence: 93%
“…Many observational studies, but only a few small randomized clinical studies, have specifically investigated the impact of educational programs on adherence to warfarin [10,11]. While several observational studies have assessed adherence to NOACs [12][13][14][15][16][17][18][19], no studies have investigated the impact of education on NOAC adherence in patients with NVAF.…”
Section: Study Proceduresmentioning
confidence: 99%
“…Studies using self-reporting (2, 3) and prescription claims data (1) yielded discrepant results on the extent of non-adherence and failed to identify concrete predictors. Although electronic monitoring is considered the most accurate method in adherence research (4), data remain scarce (5).…”
Section: Background and Aimsmentioning
confidence: 99%